2015
DOI: 10.1007/s00405-015-3830-3
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal symptoms in patients with chronic obstructive pulmonary disease

Abstract: The frequency and severity of laryngopharyngeal symptoms is significantly higher in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…We assessed LPR by monitoring laryngopharyngeal pH [19] and we could demonstrate that the prevalence of LPR is high in COPD patients (65.8%). This is in agreement with the study of Hamdan et al [13], where the RSI questionnaire was utilized to determine the presence of LPR in 27 COPD patients and 67% of them scored positive for LPR. In our study, there was no association between LPR and clinically relevant COPD outcomes within a 2-year follow-up period, contrary to the findings of Jung et al [17], who found an association between the RSI score, the reflux finding score and severe exacerbations in 118 COPD patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We assessed LPR by monitoring laryngopharyngeal pH [19] and we could demonstrate that the prevalence of LPR is high in COPD patients (65.8%). This is in agreement with the study of Hamdan et al [13], where the RSI questionnaire was utilized to determine the presence of LPR in 27 COPD patients and 67% of them scored positive for LPR. In our study, there was no association between LPR and clinically relevant COPD outcomes within a 2-year follow-up period, contrary to the findings of Jung et al [17], who found an association between the RSI score, the reflux finding score and severe exacerbations in 118 COPD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Laryngopharyngeal reflux (LPR) represents an extra-esophageal manifestation of GERD. The reflux of gastric contents is fundamental in both LPR and GERD, but the mechanism and the symptoms of the disorders are distinct [ 13 15 ]. LPR occurs when gastric contents pass the upper esophageal sphincter and usually occurs during daytime in the upright position, while GERD occurs when gastric contents pass the lower esophageal sphincter and takes place more often in the supine position at night-time or during sleep [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,26,27 Surprisingly, non-laryngologists seem to be unaware about the role of LPR in bronchial diseases such as asthma; however, many studies have demonstrated that LPR is involved in the development of bronchial hypersensitivity conditions, such as asthma, 28,29 or chronic obstructive pulmonary disease. 30 In the current survey, the largest differences between laryngologists and non-laryngologists concern diagnostic approach towards LPR, particularly with regard to examinations such as esophagoscopy and MII-pH. In initial evaluation, non-laryngologists more frequently perform or refer for esophagoscopy, although less than 40% of LPR patients have GI findings such as hiatal hernia or esophagitis.…”
Section: Discussionmentioning
confidence: 97%
“…However, studies have also shown that gastrooesophageal reflux may heighten respiratory symptoms in patients with COPD. These possible mechanisms behind gastrooesophageal reflux‐induced airway symptoms have increased recognition that gastric refluxate and nerve reflexes can be risk factors for many respiratory symptoms, including chronic cough and AECOPD (Hamdan et al., ) (Theodoropoulos, Pecoraro, & Efstratiadis, ). In both animal and clinical data, it was observed that gastrooesophageal reflux symptoms may evoke bronchospasms which heighten bronchial reactivity, changes in airway resistance and a vagal oesophageal–bronchial reflex resulting in bronchoconstriction (Field, ; Kollarik & Brozmanova, ).…”
Section: Introductionmentioning
confidence: 99%